Bentuk dan Fungsi Musik Dol pada Masyarakat Kota Bengkulu - Irfan Kurniawan; Zelly Marissa Haque (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
This article discusses the form and function of Dol music in Bengkulu city society. This study uses qualitative methods, data collection is done by observation, interviews, and documentation. The results of this study indicate that Dol music is an important element integrated in the Tabot ritual procession in the city of Bengkulu. 3 Dol music reporters in carrying out Tabot rituals, namely tamatam, swena, and sweri. The role of Dol music in the procession is to express the musical spirit of ritua tabot namely struggle, war and sadness. The existence of Dol music performance both in the context of Tabot rituals, as well as its development outside the Tabot event contest, has important values and functions for the community namely; 1) Functioning as entertainment for the community, 2) The function of emotional disclosure, seen from the emotional overflow of players in the “beruji Dol” 3) functions as a ratification of social institutions, in this case Dol music is an important requirement in the Tabot ceremony, 4) symbolic function, as a symbol manifested through musical aspects expressing sadness or the spirit of warfare, 5) the function of community integration, uniting the community in togetherness and being involved in the wisdom of the Tabot ceremony, and 6) the function of cultural continuity; the existence of Dol music as a form of effort to preserve and strengthen the cultural identity of the people of Bengkulu city.